2008
DOI: 10.1080/09585200802383455
|View full text |Cite
|
Sign up to set email alerts
|

Post-Asian financial crisis reforms: an emerging new embedded-relational governance model

Abstract: The late 1980s and early 1990s saw rapid economic growth and subjugation of social policy and environmental concerns, as development was driven through the corporate and financial sectors in East and Southeast Asian economies, fuelled by free market reforms as societies edged towards neo-liberalism. The Asian financial crisis was the catalyst for the emergence of a new embedded-relational governance model, which emphasises the social and environmental dimensions of the welfare state, while relying on decentral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The most studied countries from Europe were United Kingdom, France, Italy, Finland and Germany. Within the sample, studies were found that perform a comparative analysis between countries, such as: Germany, France, and the United Kingdom (Barbu et al, 2014a), between Germany, France, United Kingdom, Canada, Japan, United States, and India (Freedman and Jaggi, 2011), between South Korea, Malaysia, Philippines, Thailand, and Indonesia (Loftus and Purcell, 2008) and studies that involve more than 13 countries (Bozzolan et al, 2015;Liesen et al, 2015;Barkemeyer et al, 2014;Luo et al, 2012;Kolk et al, 2008).…”
Section: Industrial Sector and Countriesmentioning
confidence: 99%
“…The most studied countries from Europe were United Kingdom, France, Italy, Finland and Germany. Within the sample, studies were found that perform a comparative analysis between countries, such as: Germany, France, and the United Kingdom (Barbu et al, 2014a), between Germany, France, United Kingdom, Canada, Japan, United States, and India (Freedman and Jaggi, 2011), between South Korea, Malaysia, Philippines, Thailand, and Indonesia (Loftus and Purcell, 2008) and studies that involve more than 13 countries (Bozzolan et al, 2015;Liesen et al, 2015;Barkemeyer et al, 2014;Luo et al, 2012;Kolk et al, 2008).…”
Section: Industrial Sector and Countriesmentioning
confidence: 99%